2012
DOI: 10.1080/08856257.2011.645587
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive classrooms in Italy and England: the role of support teachers and teaching assistants

Abstract: Various models of providing for the inclusion of children with disabilities and special needs exist in different European countries. Central to all these models is the notion that support for children and teachers is pivotal in ensuring effective inclusion. This article draws from three qualitative studies on the role, employment and deployment of support teachers in Italy and teaching assistants in England to examine similarities and differences between the two models of provision. The analysis of questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 18 publications
2
30
0
9
Order By: Relevance
“…The results show that only 54.2% of the support teachers saw themselves as true teachers, whereas 13.4% of the support teachers in the sample felt that they did not have a well-defined role and that 13.9% felt that they were acting merely as an assistant to students with disabilities (TreeLLLe, Caritas, and Agnelli 2011). Devecchi et al (2012) in their article focus on the role of support teachers and teaching assistants in a comparative perspective, analysing similarities and differences between Italy and the UK. The feeling of being 'second-class' members of the school staff emerges in both countries.…”
Section: Introductionmentioning
confidence: 98%
“…The results show that only 54.2% of the support teachers saw themselves as true teachers, whereas 13.4% of the support teachers in the sample felt that they did not have a well-defined role and that 13.9% felt that they were acting merely as an assistant to students with disabilities (TreeLLLe, Caritas, and Agnelli 2011). Devecchi et al (2012) in their article focus on the role of support teachers and teaching assistants in a comparative perspective, analysing similarities and differences between Italy and the UK. The feeling of being 'second-class' members of the school staff emerges in both countries.…”
Section: Introductionmentioning
confidence: 98%
“…Two studies reported that TAs also are involved in teaching larger groups of students (Patterson, 2006;Suter & Giangreco, 2008). Other instructional responsibilities of TAs reported by TAs and educators included assessing student performance (Devecchi et al 2012), fostering peer interactions (Carter et al, 2008;Gibson et al, 2014), facilitating information sharing among educators and with families (Fisher & Pleasants, 2012), preparing and adapting materials (Liston et al, 2009), advocating for students (Howard & Ford, 2007), and promoting self-determination skills (Lane et al, 2012). Studies examining the perspectives and experiences of students with disabilities regarding their experiences with TAs provide confirmation that TAs are performing these varied instructional roles, and assuming major responsibilities for educating students with disabilities (Rutherford, 2012;Tews & Lupart, 2008;Ward, 2011).…”
Section: Research Questionmentioning
confidence: 99%
“…In the case of assistance in a group of pupils with health disabilities, the emphasis is on the higher education of teachers. The level of education of assistants working in classes with pupils with social disadvantages is not a preferred condition (Bartoňová & Pipeková, 2008;Devecchi et al, 2012;Drotárová, 2006;Giangreco & Doyle, 2007;Giangreco, 2010). The authors define an adequate level of education and knowledge, empathy, tolerance and positive and open attitude towards pupils as the most important preconditions for the work of a teacher assistant.…”
Section: Resultsmentioning
confidence: 99%